A Waqf Performance Index to Enhance Waqf Governance - Nonie Afrianty; Mesi Herawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The effective governance of waqf institutions remains a persistent challenge in Indonesia, particularly at the regional level where standardized and context-sensitive performance measurement instruments are limited. This study aims to develop a Regional Waqf Performance Index (WPI) as a governance evaluation tool for waqf institutions in Bengkulu Province, adapted from and extending the National Waqf Index framework. Employing a qualitative research design, the study integrates a literature review with Focus Group Discussions (FGDs) involving five experts representing regulators, academics, and waqf practitioners. The Analytical Hierarchy Process (AHP) is applied to determine the priority weights of governance dimensions and indicators. The findings reveal that result/outcome is the most influential dimension of waqf governance performance, particularly the productive waqf ratio, followed by the impact dimension, which reflects socio-economic benefits such as infrastructure development and community welfare. Institutional capacity, operational processes, governance systems, and regulatory support function as critical enabling factors but are not perceived as ultimate indicators of governance success. Based on these results, the study formulates an integrated WPI Governance Model that illustrates the causal relationship between governance enablers, productive outcomes, and socio-economic impacts. The proposed WPI provides a structured, measurable, and policy-ready framework that supports evidence-based decision-making, enables performance monitoring, and strengthens the accountability and developmental role of waqf institutions at the regional level.